2013
DOI: 10.1021/jp409980k
|View full text |Cite
|
Sign up to set email alerts
|

Does the Reconstitution of RC-LH1 Complexes fromRhodopseudomonas acidophilaStrain 10050 into a Phospholipid Bilayer Yield the Optimum Environment for Optical Spectroscopy?

Abstract: We have investigated reaction-center light-harvesting 1 (RC-LH1) complexes from Rhodopseudomonas (Rps.) acidophila in detergent buffer solution and reconstituted into a phospholipid bilayer and compared the results with the outcome of an earlier study conducted on RC-LH1 immobilized in polyvinyl alcohol (PVA). The aim of this study was to test whether the immobilization of the complexes in a PVA matrix might lead to a deterioration of the proteins and thereby limit the accessible information that can be obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Recently, however, the possibility of a static deformation of LH2 complexes due to the PVA matrix has been discussed in (36). To verify whether embedding the LH2 complexes in a PVA matrix deforms the structure of these antenna complexes and, therefore, introduces, per se, significant changes in their spectroscopic behavior, we reconstituted LH2 and RC-LH1 into a lipid bilayer and compared the spectra with those from complexes that were embedded in PVA (30,67). These studies revealed that at least for the LH complexes from purple bacteria, PVA is a good choice as a matrix that does not influence the conclusions drawn about the excitonic states in those pigment-protein complexes.…”
Section: The Influence Of Spectral Diffusionmentioning
confidence: 99%
“…Recently, however, the possibility of a static deformation of LH2 complexes due to the PVA matrix has been discussed in (36). To verify whether embedding the LH2 complexes in a PVA matrix deforms the structure of these antenna complexes and, therefore, introduces, per se, significant changes in their spectroscopic behavior, we reconstituted LH2 and RC-LH1 into a lipid bilayer and compared the spectra with those from complexes that were embedded in PVA (30,67). These studies revealed that at least for the LH complexes from purple bacteria, PVA is a good choice as a matrix that does not influence the conclusions drawn about the excitonic states in those pigment-protein complexes.…”
Section: The Influence Of Spectral Diffusionmentioning
confidence: 99%
“…Since in the ABEL trap the feedback signal that compensates for the diffusion of the protein is generated from the emission of the sample, the observation times are typically limited to some ten seconds before the particle crosses over to the off state and gets lost from the trap. It is, however, possible to extend the observation time by immobilizing LH2 in a polymer film under conditions where this does not significantly perturb the structure of the protein 31,32 . This approach has enabled us to follow the dynamics of the LH2 fluorescence intermittency over an unprecedented nine orders of magnitude in time.…”
Section: Introductionmentioning
confidence: 99%
“…acidophila immobilized in DDM/PVA (grey) and reconstituted into a DOPC lipid bilayer (red). Data from [64].…”
Section: Excitation Energy Transfer In a Single Photosynthetic Unitmentioning
confidence: 99%
“…acidophila into a phospholipid rsif.royalsocietypublishing.org J. R. Soc. Interface 15: 20170680 bilayer and compared the results with those obtained from LH complexes immobilized in a polymer [64,65]. Of course, singlemolecule spectroscopy cannot solve structures but it allows the distributions of spectral parameters to be obtained rather than their moments only, which is what one would obtain from (sub-) ensemble techniques.…”
Section: Spectroscopy Of Individual Rc-lh1 Complexesmentioning
confidence: 99%